Connecting - Helen Walker; Wanda Njoya; Ann Wachira; David Bedsole; W. Keith Duffy (Journal of the Assembly for Expanded Perspectives on Learning, 2015)
Helen Walker - Widening Circles Wanda Njoya - Miracles Happen Ann Wachira - Using a Model David Bedsole - To the Dog Next Door Who Barks All Day W. Keith Duffy - Aisle Four: Ice Cream, TV Dinners, Humility